MAPPING WHISTLEBLOWING THROUGH THE ROLE OF WHISTLEBLOWERS: A BIBLIOMETRIC ANALYSIS - Pinasty, Raisha Jihad Denia; Setyorini, Christina Tri (RISET: Jurnal Aplikasi Ekonomi Akuntansi dan Bisnis, 2024)
This study explores whistleblowing's role in addressing fraud and corruption in Indonesia. Using bibliometric analysis, we examined publication trends, document types, subject areas, influential authors, and critical topics in whistleblowing research from 2014 to 2023. Data were collected from the Scopus database, analyzed with the Publish or Perish application, and visualized using a VOS viewer. The results show that articles dominate the field, making up 80.25% of total citations. The findings have significant implications for policymakers, practitioners, and academics. It is a beneficial overview of whistleblowing research, but it only needs to be better and measured based on these findings. These insights do not offer actionable guidelines or strategies but work as, at most, a compass map of existing research trends and areas of interest in whistleblowing discussions. However, the lessons could form a valuable database for anyone to understand the current status of the research ecosystem. However, more than insights alone need to be directly translated into practical designs or applications like building up a system for whistleblowing and anti-fraud, et cetera, which would require further (more applied) studies.